Transformasi Uang Belanja Menjadi Investasi : Pendampingan Perencanaan Keuangan Keluarga Bersama TPFx Surabaya - Prayoga, Muhammad Rafi; Zawawi, Zawawi (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Financial instability among housewives in Surabaya is primarily rooted in two areas : deficient internal cash flow management (resulting in consumptive spending) and a lack of awareness regarding external economic threats like Inflation and Global Volatility. This lack of literacy prevents them from seeking reliable financial alternatives, leaving them exposed to investment scams. This Community Service (PkM) initiative aims to fundamentally transform grocery money into secure investment capital through intensive education and technical guidance by TPFx. The method combined basic financial literacy with hands-on risk management training, specifically demonstrating the Stop Loss feature on a futures trading simulation account. The participation of 30 housewives yielded a crucial outcome : a significant paradigm shift. Participants transitioned from investment fear to confidence, gaining the practical ability to allocate micro-capital and ensure its protection. This synergy between academics and practitioners is validated as an effective strategy for empowering family economies, uniquely focusing on the security and preservation of capital against economic risks.